Education Theory and Pedagogy for Practical Library Instruction: How to Learn What We Really Need to Know - Molly Montgomery (Communications in Information Literacy, 2015)
The majority of librarians who have taken on instruction responsibilities have had little to no formal training in educational theories or pedagogical practices. We do the best we can without a foundation for our teaching. This Perspectives column looks at how much theory we really need to know, and how can we gain this knowledge in order to become effective and engaging instructors.